A cross‐sectional study of pediatric hidradenitis suppurativa and the value of the International Hidradenitis Suppurativa Severity Score System (IHS4) as a pediatric clinical trial inclusion criteria. Issue 5 (29th June 2022) - Bui, Helen; Sayed, Christopher
Abstract: Background: Hidradenitis suppurativa (HS) often develops in pediatrics, but few interventional studies include pediatric patients. Objectives: This dual analysis of a pediatric HS cohort and typical eligibility criteria in adult trials aims to identify potential patient characteristics and inclusion criteria for future pediatric HS studies. Methods: This cross‐sectional and descriptive study is based on a prospectively collected data registry from an HS clinic. We also queried 125 HS studies from the Clinicaltrials.gov database and information from 61 interventional systemic HS drug trials was analyzed. Results: The mean abscess and inflammatory nodule (AN) count in 81 pediatric subjects was 2.3 compared to 5.0 in adults with majority being Hurley stage I (39.5%, 32/81) or II (55.6%, 45/81). Most clinical trials required patients to be Hurley stage II/III with AN count of ≥3. Conclusion: When developing clinical trials for pediatric HS, it is imperative to consider how baseline characteristics impact recruitment and disease assessment. Frequently used eligibility criteria in adult trials may severely limit pediatric recruitment. Although our registry had a large adult sample size, the main limitation of this study was the relatively smaller pediatric sample size.